The EU through multiple crises : representation and cohesion dilemmas for a "sui generis" polity - Cotta, Maurizio, 1947-; Isernia, Pierangelo (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explores the mechanisms of political representation and accountability in the European political system, against the backdrop of multiple crises in recent years in the economic, financial, security and immigration fields, which have triggered strong tensions and centrifugal drives inside the EU and among its Member states. Exploiting a rich set of new ad hoc collected data covering elite and public opinion orientations and party positions, it investigates how the current politicization of European issues and the asymmetries among member states can challenge the sustainability of the European Union. It examines how existing policy tools were found largely unable to neutralize promptly the negative effects of these crises on the populations, economies and security of the Union and how this suggests the need to reconsider overarching theoretical frameworks and a more in-depth analysis of some crucial mechanisms of the European political system and to go beyond some of the dominant scholarly debates of the past decades. This book will be of key interest to scholars and students of European Union and more broadly to comparative European politics and international relations"--
OCLC-licensed vendor bibliographic record.
Keywords: European Union countries -- Politics and government; Representative government and representation -- European Union countries; POLITICAL SCIENCE / General